Inovasi Pelayanan Kesehatan Kelas Imud Di Puskesmas Padang Pasir, Kecamatan Padang Barat, Kota Padang, Sumatera Barat - Maisy Triwahyuni; Roni Ekha Putera; Wewen Kusumi Rahayu (Universitas Teuku Umar, 2020)
IMUD Class is an innovation in health service conducted by the Padang Pasir Public Health Center, Padang Barat District, Padang City, West Sumatera. The IMUD Class innovation is a platform for pregnant women and has a baby under the age of 20 years. This innovation aims to reduce maternal and infant mortality rates especially young mothers under the age of 20 years. The formulation of the problem of this study is how the IMUD Class initiated by the Padang Pasir Public Health Center, Padang Barat District, Padang City, West Sumatera. To describe and analyze IMUD Class using the theory Innovation of Attributes proposed by Everett. M. Rogers. Rogers said that five characteristics would be able to depict an innovation that would be accepted and adopted by the public. Those characteristics are relative advantage, compatibility, complexity, trialability, and observability. This study uses a descriptive qualitative research method with the data collection methods of interview, documentation, and observation about the innovation of the IMUD Class in Padang Pasir Public Health Center, Padang Barat District, Padang City, West Sumatera. Based on the theory attributes of change, the IMUD Class at Padang Pasir Public Health Center as a whole has fulfilled the characteristics that must be possessed by an innovation.